Transgender Identities Towards a Social Analysis of Gender Diversity - Hines, Sally; Sanger, Tam (Routledge research in gender and society, 2010)
Transgender Identities: Towards a Social Analysis of Gender Diversity emerges from, and speaks to, recent sociological considerations of 'transgender.' The term 'transgender' denotes a range of gender experiences, subjectivities and presentations that fall across, between or beyond stable categories of 'man' and 'woman.' 'Transgender' includes gender identities that have, more traditionally, been described as 'transsexual,'1 and a diversity of genders that call into question an assumed relationship between gender identity and presentation and the 'sexed' body.